Viologen-Immobilized 2D Polymer Film Enabling Highly Efficient Electrochromic Device for Solar-Powered Smart Window - Wang, Zhiyong; Jia, Xiangkun; Zhang, Panpan; Liu, Yannan; Qi, Haoyuan; Zhang, Peng; Kaiser, Ute; Reineke, Sebastian; Dong, Renhao; Feng, Xinliang (Advanced Materials, 2022)
Electrochromic devices (ECDs) have emerged as a unique class of optoelectronic devices for the development of smart windows. However, current ECDs typically suffer from low coloration efficiency (CE) and high energy consumption, which have thus hindered their practical applications, especially as components in solar-powered EC windows. Here, the high-performance ECDs with a fully crystalline viologen-immobilized 2D polymer (V2DP) thin film as the color-switching layer is demonstrated. The high density of vertically oriented pore channels (pore size ≈ 4.5 nm; pore density ≈ 5.8 × 1016 m-2) in the synthetic V2DP film enables high utilization of redox-active viologen moieties and benefits for Li+ ion diffusion/transport. As a result, the as-fabricated ECDs achieve a rapid switching speed (coloration, 2.8 s; bleaching, 1.2 s), and a high CE (989 cm2 C-1), and low energy consumption (21.1 µW cm-2). Moreover, it is managed to fabricate transmission-tunable, self-sustainable EC window prototypes by vertically integrating the V2DP ECDs with transparent solar cells. This work sheds light on designing electroactive 2D polymers with molecular precision for optoelectronics and paves a practical route toward developing self-powered EC windows to offset the electricity consumption of buildings.
CRIS-Team Scopus Importer:2022-04-14